2004
DOI: 10.4028/www.scientific.net/msf.457-460.297
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Ge Coverage Prior to Carbonization on the Structure of SiC Grown on Si(111)

Abstract: A structural study of SiC layers grown by molecular beam epitaxy on carbonized Si(111) substrates with Ge modified interfaces is reported. Different quantities of Ge were predeposited prior to the SiC growth for comparison. X-ray diffraction (XRD), secondary ion mass spectrometry (SIMS), Fourier-transform infrared spectroscopy (FTIR), transmission electron microscopy in both conventional (CTEM) and high-resolution modes (HREM) and selected-area electron diffraction (SAED) have been used to evaluate the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…6 The stress reduction in the heteroepitaxial system may also be the cause of the carbon distribution confinement within the Ge segregation layer when a critical Ge content is reached (Fig. 2).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…6 The stress reduction in the heteroepitaxial system may also be the cause of the carbon distribution confinement within the Ge segregation layer when a critical Ge content is reached (Fig. 2).…”
Section: Resultsmentioning
confidence: 98%
“…The density of the dislocations is around 10 11 cm 2 . 6 Under these conditions independently of the precursors and growth techniques used in the beginning of the growth process a Si 1 x C x solid solution is formed. 7,8 If in this layer SiC nucleates then the compressive stress in the Si matrix pushes Si atoms from lattice sites into interstitial positions.…”
Section: Resultsmentioning
confidence: 99%
“…[45,57] As a consequence of the reduced stress in the initial conversion stages during the carbonization process of Si, the stress in the epitaxial 3C-SiC layer grown on top of these substrates is lowered and the crystalline quality is improved. [59,61] By increasing the Ge amount (≥1 ML), the stress keeps a decreasing behavior but the crystalline quality is deteriorated.…”
Section: C-ge-si Layer With Sic Formationmentioning
confidence: 99%
“…For this purpose, Ge [42][43][44][45][46][47][48][49][50][51][52][53][54][55] or antimon (Sb) [56] were applied to improve the 3C-SiC nucleation and the 3C-SiC interface quality. In previous works, [57][58][59][60][61][62][63] it has been demonstrated that, if Ge impurity was predeposited onto the Si surface prior to the carbonization, the residual stress inside the 3C-SiC layer, as well as the reverse currents of the SiC/Si heterojunction and the void density at the interface can be significantly reduced. In addition to the aforementioned results, it has been shown that by introducing Ge, the crystalline quality could be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, growth experiments carried out between 2 and 4 ML of Ge predeposition led to deteriorated surfaces that had detrimental effects on the subsequent epitaxial growth. 15,16 These experimental findings indicate that Ge behaves as an active diffusion barrier, which improves the crystal quality and the electrical properties. Such secondary effects can lead to an opposite effect of the Ge precoverage.…”
mentioning
confidence: 94%